COMPARATIVE STUDY OF VERNACULAR HOUSE TECTONICS IN GUBUGKLAKAH VILLAGE, TENGGER AND IN PEDAWA VILLAGE, BALI - I Gusti Ngurah, Tri Adi Citarsa; Tri Anggraini, Prajnawrdhi; I Wayan, Wiryawan (Border: Jurnal Arsitektur, 2024)
This article is a summary of research activities with a focus on comparative studies related to aspects of structural and construction systems applied in vernacular buildings in Gubugklakas Village, Tengger, East Java and in Pedawa Village, Buleleng, Bali. The aspects that are observed, are related to the structural system contained in the three segments of the building, namely in the substructure or building foundation, the superstructure or the building body, and the upper structure or roof of the building. This research was carried out using a comparative method which focus on the study regarding the structural system, loading logic, and construction system applied in the two vernacular buildings of residential houses in the two areas. The conclusions obtained are related to the characteristics of the loading logic, the construction system, the anticipation of loads and natural phenomena, as well as the building materials applied in the vernacular residential structure system in the two villages.